Short uncemented femoral component for hip revision: prognosis and risk factors associated with failure - Liu, Zeming (BMC Surg, 2021)
BACKGROUND: The application of short femoral stems is partially restricted in revision surgery. This study will demonstrate the therapeutic effect and unsuitable situation for short stem revision. METHODS: Demographic characteristics of all patients were recorded in detail (Table 1). Anteroposterior view radiographic examinations of proximal femur are necessary before and after the operation for patients. The primary outcome of interest was the survival rate of the femoral stem at the final follow-up. Risk factors for failure were also investigated. The secondary outcomes of interest included the Harris hip score, excellent to good rate and incidence of complications. The Mann–Whitney U test was performed for comparisons between continuous variables. The chi-square test was performed for comparisons between categorical variables. Cox regression analysis was used to assess the association between potential risk factors and the failure of revision surgery. RESULTS: A total of 381 patients with short stems were retrospectively reviewed. There were 188 males and 193 females. The average age and body mass index before revision surgery were 58.85 ± 13.46 years and 23.72 ± 3.40 kg/m(2), respectively. The mid-term survival rate of the short femoral component was 94.23%. The prognosis and complications of patients between the two groups were compared. There was no significant difference between the two groups in the Harris score, complication incidence or survival rate of the femoral component. The strongest risk factor in this study was intraoperative periprosthetic femoral fracture during revision surgery (HR = 5.477, 95% CI = 2.156–13.913). CONCLUSION: Three risk factors for failure were identified: ageing, osteoporosis and intraoperative periprosthetic femoral fracture during revision surgery. Therefore, a short femoral stem should be implanted in patients with these risk factors with additional caution.